Applying authoritative knowledge to better understand preparation for breastfeeding - Butler, Margaret S.; Young, Sera L.; Keenan-Devlin, Lauren (Frontiers in Global Women's Health, 2025)
IntroductionIn this qualitative study, we employ the construct of authoritative knowledge to better understand how birthing people prepare for breastfeeding experiences postpartum. This construct has seldom been applied to the postpartum period, despite its application by reproductive anthropologists to pregnancy and childbirth experiences cross-culturally. Consistent with these applications, we define authoritative knowledge domains by the purveyors. We aimed to characterize the acquisition and valuation of information sources participants used to prepare for breastfeeding.MethodsTwenty-five participants were recruited from a hospital-based pregnancy study in Chicagoland, Illinois, USA to complete interviews between November 2020 and March 2021. Audio recorded interviews were coded using a priori themes and iterative code development. Codes were used to characterize information sources and the designation of three domains of authoritative knowledge: biomedical, social network, and lived experience.ResultsAll participants received information about breastfeeding from both biomedical and social network domains, with those with prior child rearing experiences also using the personal experience domain. Use of online resources like pregnancy tracking apps and social media platforms resulted in the domains of authoritative knowledge overlapping. Participants valued information from health care providers the most but found social network information was more accessible and fulfilled their desire for experiential information.DiscussionIn this first application of authoritative knowledge within the context of infant feeding, participants consistently cited biomedical sources as the most accurate and important. However, they cited barriers to gaining this information such as the short duration of prenatal appointments and the challenge of completing prenatal education courses. Many participants sought evidence-based information about breastfeeding on apps, social media, and websites, however content and quality across platforms varies significantly. This may be an avenue to improve access to reliable and helpful breastfeeding information.